Assessment of Preliminary Grafting Compatibility-Incompatibility between Local Palestinian Table-Grapevine Cultivars and Different Phylloxera (Daktulosphaira Vitifoliae) Resistant Rootstocks - Rezq Basheer-Salimia; Abdul-Jalil Hamdan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This study was conducted to assess levels of grafting-compatibility in the nursery between scions of three Palestinian local table-grapevine cultivars (Vitis vinifera) and five grapevine rootstocks resistant to phylloxera. The cultivars inspected were Halawani, Halawani-Baladi, and Red-Romi, whereas, the rootstocks were "Richter-110, B41, Ruggeri-140, Paulsen-1103, and 216/3". For comparison purpose, cuttings of the three cultivars were also grown on their own-roots. The experiment was set up in spring 2006 and, the grafting was done by using indoor tongue grafting technique. Several parameters of graft compatibility-incompatibility including: callus production at the graft union, root development, grafting success in the incubation room as well as in the nursery (the survival percentage), bud burst, and shoot length were evaluated. Results have shown a positive correlation between callus development and grafting success. Indeed, Halawani produced the best results of callus development and graft success, Halawani-Baladi was intermediate, and Red-Romi was worst. After five months in the nursery, Halawani demonstrated highest compatibility with Richter-110 (100%), Paulsen-1103 (95%), Ruggeri-140 (85%), 216/3 (85%), and B41 (80%) successful grafts. Halawani-Baladi showed medium compatibility (79% successful grafts on Richter-110, 60% on Paulsen-1103, 79% on Ruggeri-140, 80% on 216/3 and 60% on B41). Red-Romi exhibited poor compatibility (25% of successful grafts on Richter-110; 20% on Paulsen-1103; 10% on Ruggeri-140; 5.3% on 216/3 and 45% on B41).